PENGAWETAN DUA JENIS KAYU MERANTI DENGAN METODE RENDAMAN - Barly Barly; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1987)
This paper deals with an experiment  of soaking  treatment  of two meranti  wood species each with  Wolmanit CB and Koppers Formula 7. In this process three groups of  wood samples  measure 50 cm x 5 cm x 5 cm were submerged  in a bath of preservative for  three, five  and seven days. The treatability  of  the samples  were studied.  From  this study  the following   conclusions  could  be drawn:Penetration of both preservatives could be increased into red meranti when high concentration   were employed.Retention  of Koppers  Formula  7 increases on both  meranti  when high concentration   was employed.In general the such  treatment  can not be recomended  due to the result obtained  is lower  than  the treatment  spesification requirements  for housing  wood preservation.